Modulation of LPA1 receptor-mediated neuronal apoptosis by Saikosaponin-d: A target involved in depression. (1st September 2019) - Xu, Lixing; Su, Jing; Guo, Liting; Wang, Siqi; Deng, Xueyang; Ma, Shiping
Abstract: Lysophosphatidic acid (LPA) is a bioactive lipid mediator of inflammation that binds to its specific cell surface G protein coupled receptors (LPA1-6). It is reported that LPA induced cell apoptosis by targeting LPA1, while LPA1 blockade eliminated LPS-induced production of peritoneal neutrophil chemokines and cytokines. Previous studies have shown that Saikosaponin-d (SSd) mitigated depressive-like behaviors in rats exposed to chronic unpredictable mild stress (CUMS), as well as corticosterone-induced apoptosis in PC12 cells. The present study explored the role of SSd during modulating LPA1 mediated neuronal apoptosis in LPS-stimulated mice. The phenomenon that SSd alleviated LPS-induced depressive-like behaviors were observed by open field test (OPT), forced swim test (FST) and tail suspension test (TST). SSd inhibited the protein expression of LPA1 both in the CA1 and CA3 region of the hippocampus. Moreover, SSd significantly decreased the levels of RhoA, ROCK2, p-p38, p-ERK, p-p65, p-IκBα in LPS-stimulated mice as well as in LPA-stimulated SH-SY5Y cells. Additionally, SSd significantly decreased the expression of LPA1 and the degree of neuronal apoptosis in SH-SY5Y cells which were co-cultured with LPS-stimulated BV2 microglia. These results suggested that SSd improved LPS-induced depressive-like behaviors in mice and suppressed neuronal apoptosis by regulating LPA1/RhoA/ROCK2 signaling pathway. Graphical abstract: Image 1 Highlights: Saikosaponin-d alleviated LPS-induced depressive behaviors in mice. Saikosaponin-d reduced LPA1 receptor -mediated neuronal apoptosis under condition of LPS stimulus. Saikosaponin-a promoted the neuronal survival by regulating LPA1/RhoA/ROCK2 signaling pathway.